Analysis of Phytochemical Constituent of the Volatile Oil in the Wedelia biflora by HS-SPME/GC-MS - Yang, Chao-Feng; Huang, Yu-Qiu; Yuan, Ke (Asian Journal of Chemistry, 2013)
To analyze the chemical constituents of the volatile oil in the green peel of Wedelia biflora, the chemical constituents was extracted from the Wedelia biflora by solid-phase microextraction. The chemical constituents of the volatile oil separated and identified by GC-MS. The relative content of each component was determined by area normalization. Seventy-two kinds of components were separated. Among them, 68 components were identified, accounting ca. 98.51 % of the total chemical constituents, most of them belonged to sesquiterpenoids, the main chemical constituents of the Wedelia biflora are D-limonene (15.40 %); 4,11,11-trimethyl-8-methylene-[1R-(1R*,4Z,9S*)]-bicyclo[7.2.0]undec-4-ene (9.70 %); 1R-a-Pinene (8.94 %); 4-methyl-1-(1-methylethyl)-didehydro derive bicyclo[3.1.0]hexane (8.07 %); 1-methyl-3-(1-methylethyl)-benzene (6.71 %); 1,1,4,8-tetramethyl- cis, cis, cis-4,7,10- cycloundecatriene (5.39 %); germacrene D (4.65 %), etc. The result of the experiments can provide reference for further research on the chemical components of Wedelia biflora volatile oil as well as for the exploration and utilization of it.